Teori Keperawatan Myra Estrin Levine dan Aplikasinya - Mila, Mila; Nursanti, Irna (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
Myra Estrin Levine, a well-known nurse and theorist developed several nursing theories, one of the most famous of which is Conservation Theory, in 1967. This research describes Myra Estrin Levine's nursing theory, and the application of this theory to face the challenges of complex nursing management in society modern.